1994
DOI: 10.1177/030006059402200504
|View full text |Cite
|
Sign up to set email alerts
|

Twice-Weekly Dosing for Thyroxine Replacement in Elderly Patients with Primary Hypothyroidism

Abstract: Seven female patients (mean age 86 years) with proven biochemical primary hypothyroidism were enrolled in a single-blind randomized crossover study, of standard daily versus twice-weekly thyroxine therapy, with each phase of one month's duration. The median daily dose of thyroxine was 100 micrograms (range 75-100 micrograms). Serum levels of thyroid hormones and thyrotrophin were very similar during twice-weekly thyroxine therapy to those during daily therapy and there were no statistically significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…(16). In another study, treatment with LT4 twice a week showed no statistically significant differences in thyroid hormones and in systolic time intervals, when compa red to daily treatment (22), as observed in our study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…(16). In another study, treatment with LT4 twice a week showed no statistically significant differences in thyroid hormones and in systolic time intervals, when compa red to daily treatment (22), as observed in our study.…”
Section: Discussionsupporting
confidence: 74%
“…Some recent series evaluating hypothyroid patients with poor control have shown that adequate thyroid hormone levels were obtained after introducing weekly LT4 (17,19,20,22). However, cardiovascular side effects were not thoroughly investigated in these reports.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al compared once daily versus twice weekly thyroxine treatment in seven female patients. The trough and peak serum concentrations of FT4, T3 and TSH were similar 9. Grebe et al compared daily T4 treatment with once weekly dosing in 12 hypothyroid patients in a randomised crossover trial.…”
Section: Discussionmentioning
confidence: 89%
“…This is also seen in other studies incorporating weekly and alternate day strategies to combat non compliance and to reduce costs in the treatment of sub clinical hypothyroidism. [9][10][11][12]…”
Section: Effects On Thyroid Profilementioning
confidence: 99%